Video Modeling-Based Learning for Children with Autism Spectrum Disorder (Case Study at SKH Elmyra Shanum, Serang City, Banten) - Humaeni, Ayatullah; Hadisaputro, Sami'an; Julaiha, Eka; Afif, Muhamad (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This study aims to describe the implementation of video modelling-based learning for children with Autism Spectrum Disorder (ASD) and interpret the experiences of teachers and students in the context of special education units. Children with ASD are known to benefit greatly from structured and repeatable visual learning strategies, while video modelling has been recognized as an evidence-based practice for teaching a wide range of social, academic, and independence skills. The research used a qualitative approach with an intrinsic case study design at SKH Elmyra Shanum Serang City, Banten, which involved special education teachers, several ASD students, and parents as the main participants. Data were collected through participatory observation of learning sessions, in-depth interviews, and document studies, then analized thematically through the stages of reduction, presentation, and drawing conclusions by triangulating sources and methods to maintain the validity of the findings. The results of the study show that video modelling is interpreted by teachers as a medium that facilitates the breakdown of complex skills into visual steps that are easier for ASD students to understand, increases focus and motivation to learn, and helps generalize skills to other contexts, although there are still obstacles related to technological facilities and teachers' technical competence. These findings confirm the potential of video modelling as an integral part of individualized learning programs in special schools and underscore the importance of institutional support and teacher training to optimize the use of video-based media in the education of children with ASD.